Hubungan Social Distancing Terhadap Depresi Dalam Menghadapi Wabah COVID-19 di Markas Komando Marinir Jakarta Pusat - Eko Yulianto; Saiful Gunardi; Emi Yuliza (Open Access Jakarta Journal of Health Sciences, 2021)
Introduction:  Social distancing is an effort to tackle the transmission of COVID-19. This effort has an impact on every sector of life, one of which is mental health, such as depression. Objective: The purpose of this study was to determine the relationship between social distancing and depression during Covid-19 Outbreak at the Marine Command Central Jakarta. Methods: This research method with cross sectional design on all staff of Denma Marine Command, Central Jakarta. Bivariate data analysis using Chi Square. Respondents who participated in this research were 49 staff. Results: The results showed that 61.2% of respondents had implemented social distancing and 24.5% of respondents experienced symptoms of depression. There is relationship between social distancing behavior and depressive symptoms experienced by respondents during the COVID-19 pandemic at Mako Kormar, Central Jakarta (p = 0.022). Coclusion:  there is relationship between social distancing and depressive symptoms during the COVID-19 pandemic in Mako Kormar, Central Jakarta.